Secondary Focal Segmental Glomerulosclerosis: From Podocyte Injury to Glomerulosclerosis. (21st March 2016) - Kim, Jae Seok; Han, Byoung Geun; Choi, Seung Ok; Cha, Seung-Kuy
Abstract : Focal segmental glomerulosclerosis (FSGS) is a common cause of proteinuria and nephrotic syndrome leading to end stage renal disease (ESRD). There are two types of FSGS, primary (idiopathic) and secondary forms. Secondary FSGS shows less severe clinical features compared to those of the primary one. However, secondary FSGS has an important clinical significance because a variety of renal diseases progress to ESRD thorough the form of secondary FSGS. The defining feature of FSGS is proteinuria. The key event of FSGS is podocyte injury which is caused by multiple factors. Unanswered questions about how these factors act on podocytes to cause secondary FSGS are various and ill-defined. In this review, we provide brief overview and new insights into FSGS, podocyte injury, and their potential linkage suggesting clues to answer for treatment of the disease.